Vom byzantinischen zum arabischen Ägypten Neue dokumentarische Papyri aus dem 5. bis 8. Jh. (P.Heid. XI) - Berkes, Lajos (Studien und Texte aus der Heidelberger Papyrussammlung, 2021)
This volume contains the edition of 42 Egyptian documentary papyri from the 5th-8th century AD including translations as well as historical and philological commentary. The texts were written in Greek or Coptic, but the volume also comprises bilingual Greek-Coptic documents and an Arabic-Greek protocol. These multifaceted papyri, such as administrative, legal and tax documents, allow precious glimpses into the society of the late antique Nile Valley and produce important new evidence for the underexplored transition period from Byzantine to Islamic rule in Egypt.